Responsiveness in the Swedish moose management - Löfgren, Marie (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2017)
The moose population in Sweden has historically fluctuated considerably. It has changed from a situation of near extinction to a state of overabundance. With the intent to solve some of the ecological and social problems present in the moose management, the Swedish government introduced a new moose management system in 2012. It is now supposed to be carried out in an adaptive, ecosystem- and locally based way, were the knowledge and experiences of hunters and landowners are used to manage the species. A new level of responsibility has been installed called moose management areas (MMA). The areas are governed by a moose management group (MMG) consisting of three hunters´ and three landowners´ representatives, who are supposed to represent the interests of their respective organisations. The aim of my study was to investigate the representation in the newly instated MMA´s and the component, in the concept of representation, which I mainly focused on was responsiveness. In order to investigate responsiveness, I used data from three questionnaires, which had been sent out to landowners, hunters and MMG representatives. I primarily defined responsiveness as the overlap in views, regarding the number of moose in an MMA, expressed by the local landowners´, hunters´ and their respective MMG representatives in the different questionnaires. Furthermore, I also collected several moose management plans (MMP), from the various MMAs, to be able to examine if the views of the local landowners and hunters could be observed in the plans. Moreover, to investigate if certain aspects could have an effect on responsiveness, I tested it against a number of independent variables, which I named occupation, identity, attendance at wildlife management consultation and network. Moreover, I also tested if there was significant difference in responsiveness between the landowners, hunters and the MMG representatives seen between the three regions Götaland, Svealand and Norrland of Sweden. The general conclusion that can be made from my study is that the overlap between the views of the local hunters and their MMG representatives appears to be slightly greater compared to the overlap between the views of the landowners and their MMG representatives. However, the overlap between the views of the landowners’ representatives and the development goals in the MMPs, appears to be stronger than that of the hunters´ representatives. Furthermore, the results also revealed that two independent variables presented a significant difference in responsiveness for the landowners, namely occupation and network, indicating that responsiveness may be effected if a landowner has a job in either the forestry, agriculture or wildlife management as well as if a landowner is part of a landowner organisation. Results also revealed that responsiveness, for the hunters, may be affected if a hunter is part of a hunting team. Furthermore, I detected a significant difference in the mean level of responsiveness for hunters, amongst the three regions, but could not detect any such significant difference in responsiveness for the landowners.